Analyzing Fraudulent Practices in Community Group Regional Grant Funding - Faisol, Faisol; Haryadi, Bambang; Musyarofah, Siti (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
This study investigates fraud in community group grant funds, supported by the Regional Government to enhance Provincial Government programs. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. Findings indicate a lack of genuine community involvement in forming groups, with grant proposals often requiring dubious payments to coordinators. Physical development projects frequently utilized subpar materials and did not align with initial budget plans. Additionally, there was manipulation in reporting activities, with projects funded by village funds improperly claimed as grant initiatives. Delays in the accountability reporting, influenced by postponed project execution, complicate oversight. The study underscores the necessity for stringent regulations to prevent grant fund fraud, thereby assisting the Provincial Government in maintaining the integrity of its developmental agenda. Keywords : grant funds, fraud, community groups